Efektivitas Pemberdayaan Kader Kesehatan terhadap Eliminasi Stigma bagi Penderita Tuberkulosis Paru pada Masyarakat di Kecamatan Kuta Baro Kabupaten Aceh Besar - Imam Maliki; Edhitta Deviana; Donny Hendra (Universitas Serambi Mekkah, 2020)
Provincial data on 2019 showed that there were 3,485 tuberculosis cases found in Aceh Besar. The Kuta Baro district listed as the most prevalence one compared to the other regions. Tuberculosis, in fact, remains stigmatized as contagious disease. Most of tuberculosis sufferers are isolated from community live. Health cadres involvement is most likely effective to eliminate those negative perspective. This research was aim to identify the effectiveness of health cadres on their role to eradicate negative stigma towards tuberculosis sufferers. The intervention applied in this research was series of empowerment program for the health cadres in the community where the study took place. The study design was a quasi experiment without control group. Population involved in the study was all community in Kuta Baro district, Aceh Besar. Data was collected by adopting Explanatory Modul Interview catalogue survey. Results revealed that health cadres empowerment program was effective to change community’s stigma towards tuberculosis sufferers (p = 0.0001) as well as their attitude on tuberculosis ( p = 0.0001). Finally, it can be concluded from the study that there is a need for collaboration between health professionals and community cadres to improve knowledge on tuberculosis through continuous health promotion program.Keywords: Empowerment, Health Cadres, Stigma, Tuberculosis